Phenomenology of the image: Sartre's critique of representation and its possibilities for an existential geography: (PerCursos, 2024)
Thinking about possibilities for an existential geography based on Sartre's critique of representation and the modes of image/imagination as the foundations of a phenomenology of the image is the central question of this text. To do this, we turn to the works “The Imagination” (1936) and “The Imaginary: Phenomenological Psychology of the Imagination” (1940) by the philosopher Jean-Paul Sartre, which indicates an understanding of the image as an act, in other words, the image is always a consciousness of somthing, removing from it the objectifying aspect. This undertaking by the philosopher in his early years of incorporating Phenomenology into his thinking helps us to stress the usability of the image/imagination dimension in geographical research. The text takes on a meditative character, considering in its final part the basis for an existential geography, to be thought of from the point of view of geosophy, the act of imagining as the way of phenomenologically naming things and places.
Keywords: imagination; imaginary; situationality; corporeality